Characteristics and clinical outcomes in patients with prior chest radiation undergoing TAVR: Observations from PARTNER‐2. Issue 6 (15th March 2022) - Mohanty, Bibhu D.; Coylewright, Megan; Sequeira, Ashton R.; Shin, Doosup; Liu, Yangbo; Li, Ditian; Fradley, Michael; Alu, Maria C.; Mack, Michael J.; Kapadia, Samir R.; Kodali, Susheel; Thourani, Vinod H.; et al.
Abstract: Objectives: The purpose of this study is to investigate the viability of transcatheter aortic valve replacement (TAVR) for severe symptomatic aortic stenosis (AS) in patients with prior chest radiation therapy (cXRT). Background: Since patients with prior cXRT perform poorly with surgical aortic valve replacement, TAVR can be a viable alternative. However, clinical outcomes after TAVR in this patient population have not been well studied. Methods: From the pooled registry of the placement of aortic transcatheter valves II trial, we identified patients with and without prior cXRT who underwent TAVR ( n = 64 and 3923, respectively). The primary outcome was a composite of all‐cause death and any stroke at 2 years. Time to event analyses were shown as Kaplan–Meier event rates and compared by log‐rank testing. Hazard ratios (HRs) were estimated and compared by Cox proportional hazards regression model. Results: There was no significant difference in the primary outcome between the patients with and without prior cXRT (30.7% vs. 27.0%; p = 0.75; HR, 1.08; 95% confidence interval, 0.66–1.77). Rates of myocardial infarction, vascular complications, acute kidney injury, or new pacemaker implant after TAVR were not statistically different between the two groups. The rate of immediate reintervention with a second valve for aortic regurgitation after TAVR was higher among the patients with prior cXRT. However, no further difference was observed during 2 years follow‐up after discharge from the index‐procedure hospitalization. Conclusions: TAVR is a viable alternative for severe symptomatic AS in patients who had cXRT in the past.